LncSLdb: a resource for long non-coding RNA subcellular localization. (13th September 2018) - Wen, Xiao; Gao, Lin; Guo, Xingli; Li, Xing; Huang, Xiaotai; Wang, Ying; Xu, Haifu; He, Ruijie; Jia, Chenglong; Liang, Feixiang
Abstract: While long non-coding RNAs (lncRNAs) may play important roles in cellular function and biological process, we still know little about them. Growing evidences indicate that subcellular localization of lncRNAs may provide clues to their functionality. To facilitate researchers functionally characterize thousands of lncRNAs, we developed a database-driven application, lncSLdb, which stores and manages user-collected qualitative and quantitative subcellular localization information of lncRNAs from literature mining. The current release contains >11 000 transcripts from three species. Based on the accumulated region of lncRNAs, we classify transcripts into three basic localization types (nucleus, cytoplasm and nucleus/cytoplasm). In some conditions, the nucleus and cytoplasm types can be divided into three more accurate subtypes (chromosome, nucleoplasm and ribosome). Besides browsing and downloading data in lncSLdb, our system provides a set of comprehensive tools to search by gene symbols, genome coordinates or sequence similarity. We hope that lncSLdb will provide a convenient platform for researchers to investigate the functions and the molecular mechanisms of lncRNAs in the view of subcellular localization.